Ethics on the home planet - Rolston, Holmes, 1932-2025, author; Oxford University Press, publisher (Colorado State University. Libraries, 1999)
Views of Earth from space bring us home again. Earth is to be treasured, something precious that must endure. Human desires for maximum development drive population increases, escalate exploitation of the environment, and fuel the forces of war. So we are searching for an ethics adequate to respect life on Earth. The valuing of nature is not over until we have risen to the planetary level, and valued this system we inhabit. Earth is really the relevant survival unit. This environmental ethics for the new millennium.
Keywords: plants; environmental ethics; biodiversity; life; ecosystems; mind; ethics; nature; humans; endangered species; animals; Earth